2019
DOI: 10.3390/ma12213566
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Usability of Acceleration Test by Impressed Anodic Current for Evaluating Corrosion Behavior of Hot-Dip Galvanized Rebar in Concrete

Abstract: Hot-dip Galvanized rebar (hereafter, HDG rebar) has an anti-corrosion effect due to the sacrificial anodic reaction of zinc. Additionally, the zinc coating itself provides barrier protection for the steel substrate. Meanwhile, from one of the investigations on the field performance of HDG rebar in concrete, HDG rebar did not protect the substrate when the remaining zinc was under 50 µm. For the evaluation of this property over a short period of time, an acceleration test using impressed anodic current (hereaft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Recently, researchers found that phosphating was an effective and important process applied to steels which has been successfully used in automotive industries due to easy operation and low cost [22]. The phosphating method (phosphate coats) can improve the corrosion resistance and lubrication properties of steel fibers [23] as well as steel rebars [24,25]. Among phosphate coats, zinc phosphate is the most popular coating, due to its capacity for anodic protection of Zn 2+ and barrier protection of the existing phosphate film, and, therefore, phosphate coatings have attracted more attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers found that phosphating was an effective and important process applied to steels which has been successfully used in automotive industries due to easy operation and low cost [22]. The phosphating method (phosphate coats) can improve the corrosion resistance and lubrication properties of steel fibers [23] as well as steel rebars [24,25]. Among phosphate coats, zinc phosphate is the most popular coating, due to its capacity for anodic protection of Zn 2+ and barrier protection of the existing phosphate film, and, therefore, phosphate coatings have attracted more attention in recent years.…”
Section: Introductionmentioning
confidence: 99%